PERAN ORANG TUA DALAM PEMBENTUKAN KARAKTER ANAK DI KELURAHAN TAFURE KECAMATAN TERNATE UTARA - Suharyun Suharyun; Samsu Somadayo; Fachriah Djumati (PEDAGOGIK, 2021)
This studi aims to determine the role of parents in the formation of children's character in Tafure Village, North Ternate District. The research method used in this study is a descriptive qualitative method. In collecting data using interview and documentation techniques. Respondents in this study were the village head, village priest, head of youth, and 10 parents who have children aged 7-12 years.The results showed that through interviews and documentation in the field, the role of parents in shaping the character of children in Tafure village, North Ternate sub-district, among others: (1) providing advice, giving advice to children by parents in their spare time or when children make mistakes; (2) educating through examples that aim to make children have good character because they directly follow the behavior of their parents; (3) teach and provide understanding to children in recognizing and knowing their obligations as a child; (4) train children with manners that every parent must do to instill the values of politeness and courtesy that have become customary values; (5) conduct a system of habituation of parents to children so that children become individuals who are accustomed to doing good things. This role is carried out by parents in the Tafure sub-district, North Ternate sub-district in forming character values in children which include religious values, honesty, discipline, independence, social care, environmental care, and responsibility. If seen from the results found, the role of parents in shaping the character of children in the Tafure village, North Ternate sub-district has entered the level of becoming a culture for the formation of polite and courteous attitudes, while the formation of other character values is still at the level of becoming a habit and getting used to it.